Genetic Characteristics of Multiple Copies of Tn1546-Like Elements in ermB-Positive Methicillin-Resistant Staphylococcus aureus From Mainland China - Wang, Haiping; Wu, Dandan; Di, Lingfang; Zhu, Feiteng; Wang, Zhengan; Sun, Lu; Chen, Yiyi; Jiang, Shengnan; Zhuang, Hemu; Chen, Mengzhen; Ji, Shujuan; Chen, Yan (Frontiers in Microbiology, 2022)
Objective To determine the genetic structure of ermB-positive Tn1546-like mobile elements in methicillin-resistant Staphylococcus aureus (MRSA) from mainland China. Methods A total of 271 erythromycin-resistant MRSA isolates were isolated from Sir Run Run Shaw Hospital (SRRSH) from 2013 to 2015. Whole-genome sequencing was performed for the ermB-positive strains, and the genetic environment of the ermB genes was analyzed. Southern hybridization analysis and transformation tests were performed to confirm the location of the ermB gene. Results A total of 64 isolates (64/271, 23.6%) were ermB-positive strains, with 62 strains (62/64, 96.9%) belonging to the CC59 clone. The other two strains, SR130 and SR231, belonging to CC5-ST965, both harbored 14,567 bp ermB-positive Tn1546-like elements and displayed multidrug-resistant profiles. PFGE followed by Southern blot demonstrated that the ermB genes were located on the plasmids of both SR130 and SR231, while two copies of ermB were located on the chromosome of SR231. Further sequencing demonstrated that SR231 carried one Tn1546-ermB elements in the plasmid and two identical copies integrated on the chromosome, which had 99.99% identity to the element in the plasmid of SR130. The Tn1546-ermB elements were highly similar (100% coverage, >99.9% identity) to the element Tn6636 reported in a previous study from Taiwan. The plasmids (pSR130 and pSR231) harboring ermB-positive Tn1546-like elements were also identical to the mosaic plasmid pNTUH_5066148. However, conjugation of ermB-carrying plasmids of SR130 and SR231 were failed after triple repeats. Conclusion Multiple copies of ermB-positive Tn1546-like mobile elements were found in CC5-ST965 MRSA from mainland China, showing the wide dissemination of these Enterococcus faecium-originated ermB-positive Tn1546-like elements. Molecular epidemiological study of Tn1546-like elements is essential to avoid the spreading of resistant determinants.